1999
DOI: 10.1002/(sici)1096-8628(19990129)82:3<212::aid-ajmg3>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Noonan syndrome and cavernous hemangioma of the brain

Abstract: We present two patients with multiple characteristics that occur in Noonan phenotype and cavernous hemangioma of the brain. The first patient, who had been diagnosed radiographically as having a cavernous hemangioma in the left basal ganglia at age 15 years, developed massive intracerebral hemorrhage, resulting in sudden death at home at 19 years. The second patient, who was diagnosed radiographically as having a cavernous hemangioma in the left parietal lobe at age 17 years, is being followed carefully (the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…Moschovi et al described another rhabdomyosarcoma, but no molecular analysis had been performed on this patient [16]. Tanaka et al reported a Noonan syndrome patient with a cavernous hemangioma of the brain [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moschovi et al described another rhabdomyosarcoma, but no molecular analysis had been performed on this patient [16]. Tanaka et al reported a Noonan syndrome patient with a cavernous hemangioma of the brain [32].…”
Section: Discussionmentioning
confidence: 99%
“…Suttor et al reported an association of multiorgan vascular malformations with NS (6). On the other hand, Turner's syndrome with multiorgan vascular malformations has been previously noted (7,8). In the present case, no other vascular malformation except for angioectasia in the small intestine was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to the best of our knowledge, it has not been previously described. Tanaka et al (1999), however, have recently reported cavernous hemangiomas of the brain without any cutaneous lesions in 2 patients with Noonan phenotypes. Furthermore, our patient did not fit into the phenotypic entity of CFC syndrome as he did not have the cardiovascular anomalies, hair changes, hyperkeratotic and other ectodermal lesions and cranial deformities associated with this condition (McKussick, 1988;Borradori and Blanchet-Bardon, 1993;Verloes et al, 1988;Reynolds et al, 1986).…”
Section: Discussionmentioning
confidence: 99%